Reseña bibliográfica : Grintis, Herbert (2014). The bounds of reason. Game theory and the unification of the behavioral sciences. Princeton University Press - Zemborain, Luis (2017)
Fil: Zemborain, Luis. Pontificia Universidad Católica Argentina; Argentina